Extraction-Spectrophotometric Studies on the Ion-Pairing Between Some 2,3,5-Substituted Monotetrazolium Cations and Anions Deriving from 4-(2-Thiazolylazo)resorcinol or 4-(2-Pyridylazo)resorcinol - Gavazov, Kiril Blazhev; Toncheva, Galya K. (JOURNAL OF ADVANCES IN CHEMISTRY, 2009)
The ion-pairing between some 2,3,5-substituted monotetrazolium cations (T+) and anions deriving from 4-(2-pyridylazo)resorcinol (PAR) or 4-(2-thiazolylazo)resorcinol (TAR) was studied by water-chloroform extraction and spectrophotometry. The following tetrazolium salts (TS) were used as a source of T+: i) 2,3,5-triphenyl-2H-tetrazolium chloride (TTC); ii) 3-(4,5-dimethyl-2-thiazol)-2,5-diphenyl-2H-tetrazolium bromide (MTT); iii) 3-(2-naphtyl)-2,5-diphenyl-2H-tetrazolium chloride (Tetrazolium violet, TV); and iv) 2-(4-iodophenyl)-3-(4-nitrophenyl)-5-phenyl-2H-tetrazolium chloride (INT). The spectral characteristics of the extracted species were established at different pH and TS concentration. The composition and stability of the ion-pairs were determined at pH 9, where the extraction of neutral PAR (H2PAR) and TAR (H2TAR) species was negligible. The results showed that the ion-pairs can be expressed with the following formulae (T+)(HTAR–) (where T+ = TT+, MTT+, TV+ or INT+), (T+)(HPAR–) (where T+ = TT+, MTT+ or TV+) and [(INT+)(HPAR–)]2. Relationships involving the molecular masses of the ion-pairs (MIP) or T+ (MT+) and the values of the constants of association (b) or conditional molar absorptivities (e’) were examined, namely Log b = f(Log MIP) and e’ = f(Log MT+). Some practical aspects concerning the investigation of metal complexes with TS-PAR/TS-TAR were discussed.